Radicular anatomy of twelve representatives of the Catasetinae subtribe (Orchidaceae: Cymbidieae) - Pedroso de Moraes, Cristiano (2012)
Considering that the root structure of the Brazilian genera belonging to the Catasetinae subtribe is poorly known, we describe the roots of twelve representatives from this subtribe. For anatomical analysis, the roots were fixed in FAA 50, preserved in ethanol 70% and sectioned at its medium region using razor blades. The sections were stained with 0.05% astra blue and safranin and mounted in glycerin. For the identification of starch we used Lugol ́s solution; for lignin, floroglucin chloridric; for lipids, Sudan III, and for flavanoids, potassium hydroxide. The relevant aspects were registered using a digital camera joined with an Olympus microspope (BX51 model). The structural similarities of all roots support the placement of the subtribe Catasetinae into the monophyletic tribe Cymbidieae. Some root features are restricted to one or two taxa and can be useful in the systematics of the subtribe. For example, the occurrence of flavonoidic crystals characterizes the genera Catasetum and Cychnodes, and the number of the velamen layers and the shape of the epivelamen cells are useful to confirm the taxonomic position of Clowesia amazonica. The presence of velamen and flavonoidic crystals was interpreted as an adaptation to the epiphytic habit.